Ixodes ricinus and Its Transmitted Pathogens in Urban and Peri-Urban Areas in Europe: New Hazards and Relevance for Public Health - Rizzoli, Annapaola; Silaghi, Cornelia; Obiegala, Anna; Rudolf, Ivo; Hubálek, Zdeněk; Földvári, Gábor; Plantard, Olivier; Vayssier-Taussat, Muriel; Bonnet, Sarah; Špitalská, Eva; Kazimírová, Mária (Frontiers in Public Health, 2014)
Tick-borne diseases represent major public and animal health issues worldwide. Ixodes ricinus, primarily associated with deciduous and mixed forests, is the principal vector of causative agents of viral, bacterial and protozoan zoonotic diseases in Europe. Recently, abundant tick populations have been observed in European urban green areas, which are of public health relevance due to exposure of humans and domesticated animals to potentially infected ticks. In urban habitats, small and medium sized mammals, birds, companion animals (dogs, cats) and larger mammals (roe deer, wild boar) play a role in maintenance of tick populations and as reservoirs of tick-borne pathogens. Presence of ticks infected with tick-borne encephalitis virus and high prevalence of ticks infected with Borrelia burgdorferi s.l., causing Lyme borreliosis, have been reported from urbanized areas in Europe. Emerging pathogens, including bacteria of the order Rickettsiales (Anaplasma phagocytophilum, 'Candidatus Neoehrlichia mikurensis', Rickettsia helvetica, R. monacensis), Borrelia miyamatoi and protozoans (Babesia divergens, B. venatorum and B. microti) have also been detected in urban tick populations. Understanding the ecology of ticks and their associations with hosts in a European urbanized environment is crucial to quantify parameters necessary for risk pre-assessment and identification of public health strategies for control and prevention of tick-borne diseases.